Mode hybridization in a gyrotron cavity with background plasma - Shcherbinin, V.I.; Zaginaylov, G.I. (Вопросы атомной науки и техники, 2014)
It is shown that a formation of hybrid modes (mode hybridization) in a gyrotron cavity occurs as their frequencies approach coincident points induced by background plasma. Such process, which is accompanied by a drastic change in fields and Q-values of the cavity modes, is studied with respect to some gyrotron parameters. Estimations are presented for several high-power continuous-wave (cw) gyrotrons. Показано, что формирование гибридных мод (гибридизация мод) в резонаторе гиротрона происходит по мере приближения их частот к точкам совпадения, которые формируются фоновой плазмой. Такой процесс, который сопровождается существенным изменением полей и добротностей мод резонатора, исследован в зависимости от параметров гиротрона. Оценки приведены для ряда мощных непрерывных гиротронов. Показано, що формування гібридних мод (гібридизація мод) у резонаторі гіротрона відбувається разом із наближенням їхніх частот до точок збігу, які формуються фоновою плазмою. Такий процес, який супроводжується значною зміною полів та добротностей мод резонатора, було досліджено в залежності від параметрів гіротрона. Оцінки наведено для ряду потужних безперервних гіротронів.